ALIRAN KAS OPERASI, BOOK TAX DIFFERENCES, DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA - Sabrina anindita Putri; Khairunnisa A; Kurnia M (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
Earning persistence is a component of earning quality. The purpose of this research is to determine the effect of variable operating cash flow, book tax differences, and leverage either simultaneously or partially to the variable earning persistence as well as the variable most dominant influence on earning persistence. Book tax differences variable is projected with temporary difference variable because of the differences between accounting and fiscal policy. The type of this research is descriptive verification that is causality. The number of automotive subsector manufacture companies in Indonesia Stock Exchange over the period of 2011-2015. The entered population was registered are 13 companies and sample of 10 companies. The sample selection technique used is purposive sampling. The result sing panel data regression it showed that a combination of three variables (operating cash flow, book tax difference, and leverage) can affect the earning persistence of 35%, . From the partial test results, it showed that of Operating Cash Flow and Leverage gave positive significant effect on earing persistance, while book tax differences, did not have any affect on earning persistences.